PELAKSANAAN KEWENANGAN PEMERINTAH KABUPATEN PASAMAN BARAT DALAM URUSAN KETENAGAKERJAAN TAHUN 2018 - Ori Hanifinanda; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Unemployment is a situation in which someone belonging to the labor force category does not have a job and is not actively looking for work. In this case, it is the regional government's concern in managing its own household, to reduce the number of unemployed people in West Pasaman Regency, the authority is given to the West Pasaman Regency Manpower Office as the executor of government affairs in the manpower sector.The purpose of this study is to determine the implementation of authority carried out by the West Pasaman Regency Manpower Office in 2018. The research location is in the West Pasaman Regency Manpower Office. This research uses a qualitative approach. This type of research is descriptive. Data were collected through informants purposively. Data collection techniques using interviews and documents.The results show that the implementation of authority in manpower affairs by the West Pasaman Regency Manpower Office in 2018 comes from the authority of Attribution. Exercise of authority in two sub-fields, first, in the sub-sector of job training and productivity. Second, in the sub-sector of manpower placement. Keywords: Attribution, Job Training, Job Placement